2019
DOI: 10.1007/978-3-030-29333-8_1
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Conflict Research Through Computational Approaches

Abstract: Conflict, from small-scale verbal disputes to large-scale violent war between nations, is one of the most fundamental elements of social life and a central topic in social science research. The main argument of this book is that computational approaches have enormous potential to advance conflict research, e.g., by making use of the ever-growing computer processing power to model complex conflict dynamics, by drawing on innovative methods from simulation to machine learning, and by building on vast quantities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Computational models dealing with international security have recently emerged within the field of conflict studies (see for example [ 28 ]). Statistical models had until now dominated the field [ 29 ]; while these are valuable in understanding causal dynamics and the relationship between variables, their application is generally restricted to understanding the causes of conflict [ 30 32 ] and forecasting violent outbreaks [ 33 – 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Computational models dealing with international security have recently emerged within the field of conflict studies (see for example [ 28 ]). Statistical models had until now dominated the field [ 29 ]; while these are valuable in understanding causal dynamics and the relationship between variables, their application is generally restricted to understanding the causes of conflict [ 30 32 ] and forecasting violent outbreaks [ 33 – 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…An advantage of the application of computational models is the ability to analyze the effects of military strategies ex-ante, and hence before they are used in practice. 4 For example, Chaturvedi et al 5 demonstrated the capability of agent-based modeling (ABM) to analyze the interactions of government, firms, and adversaries in (potential) information warfare scenarios. While an increased amount of available data promised a quick development of predictive models for emerging insurgent conflicts, machine learning techniques have been unable to fulfill the promise to deliver early-warning systems.…”
Section: Introductionmentioning
confidence: 99%
“…Computational models dealing with international security have recently emerged within the field of conflict studies (see for example [28]). Statistical models had until now dominated the field [29]; while these are valuable in understanding causal dynamics and the relationship between variables, their application is generally restricted to understanding the causes of conflict [30][31][32] and forecasting violent outbreaks [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%